2017
DOI: 10.1016/j.ultsonch.2016.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the influence of low-frequency and low-intensity ultrasound on the permeability of the Mycobacterium smegmatis cytoderm and potentiation with levofloxacin

Abstract: Tuberculosis is an infectious disease caused by the bacterium M. tuberculosis. The aim of this study was to investigate the bactericidal effect and underlying mechanisms of low-frequency and low-intensity ultrasound combined with levofloxacin treatment against M. smegmatis (a surrogate of M. tuberculosis). As part of this study, M. smegmatis was continuously irradiated with low frequency ultrasound (42kHz) using several different doses whereby both intensity (0.138, 0.190 and 0.329W/cm) and exposure time (5, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The use of low-frequency ultrasound (20 to 100 kHz) as a noninvasive treatment has been shown to improve cell membrane permeability, increase drug penetration, and achieve synergistic antibacterial effects by previous research (27)(28)(29). In the in vitro experiments, we demonstrated a highly effective synergistic antifungal effect of lowfrequency ultrasound combined with drug-loaded nanoparticles against C. albicans biofilms through XTT reduction assays and CLSM observation.…”
Section: Figmentioning
confidence: 68%
“…The use of low-frequency ultrasound (20 to 100 kHz) as a noninvasive treatment has been shown to improve cell membrane permeability, increase drug penetration, and achieve synergistic antibacterial effects by previous research (27)(28)(29). In the in vitro experiments, we demonstrated a highly effective synergistic antifungal effect of lowfrequency ultrasound combined with drug-loaded nanoparticles against C. albicans biofilms through XTT reduction assays and CLSM observation.…”
Section: Figmentioning
confidence: 68%
“…Currently, most studies suggest that cavitation is the main responsible cause for the synergistic e ect. Liquid medium can form microbubbles, which may act on bio lms and increase its permeability to antimicrobial agents or even kill bacteria in bio lm [22][23][24]. However, for K. pneumoniae, many studies have demonstrated that the limited penetration of antibiotic molecules through the bio lm matrix is not the main reason for the increased resistance, but rather, the slow growth rate in the center of bio lm is [1].…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of synergy is unclear. Several studies suggested that LFU cavitation was mainly responsible for the synergistic antimicrobial effect [ 14 16 ]. Under LFU treatment, liquid medium could form microbubbles, which might act on biofilms and increase its permeability to antimicrobial agents or even kill bacteria in biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, with more oxygen and nutrition entering biofilms, the susceptibility of MRSA or MSSA to antimicrobial agents may be reversed [ 18 ]. Other studies indicated that synergy may also be associated with heating or other mechanisms [ 16 , 19 ]. Overall, LFU possibly acts on the extracellular matrix of bacterial biofilm through multiple paths to facilitate the quick entrance of antimicrobial agents into biofilm.…”
Section: Discussionmentioning
confidence: 99%